Controlled release of antimicrobial Cephalexin drug from silica microparticles - Rao, B. V. Bhaskara; Mukherji, Ruchira; Shitre, G.; Alam, F.; Prabhune, Asmita; Kale, Sangeeta N. (Materials Science & Engineering C-Materials for Biological Applications, 2014)
Release of antimicrobial drugs in a controlled fashion for extended duration of time has been investigated for long. Such controlled-drug-releasing materials show promising applications in medicinal bandages. Along with antimicrobial agents, one could also incorporate other therapeutic drugs, to make such bandages more versatile. In this context, silica micro particles were synthesized using direct reduction method, in which the synthesis was done in the presence of Cephalexin. Cephalexin was chosen as an antimicrobial candidate. The morphological characterization shows formation of monodispersed, silica microparticles of similar to 200 nm in size. The FTIR spectroscopy shows weak interaction of the drug molecule at its hydroxide (OH) site with oxygen ions on the silica surface. Upon conjugation, the UV-vis spectroscopy shows persistence of the Cephalexin signature, especially its R group, confirming its antimicrobial activity even after conjugation. Loading studies reveal 12% Cephalexin loading on silica. The antimicrobial studies were done on three micro-organisms, namely, Staphylococcus aureus, Bacillus subtilis and Escherichia coli. Using zone-of-inhibition studies, it was found that E. coli, did not respond to the delivery of Cephalexin either directly or via microparticles. However, for both S. aureus and B. subtilis, the particles showed controlled release of Cephalexin for the duration of 48 h and continued maintenance and even increase in the zone of inhibition. This work demonstrates an effective protocol to prepare antimicrobial patches for controlled drug delivery. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial; Medicinal bandage; Silica microparticles; sustained drug release